Capacidade tecnológica e o processo de internacionalização das vinícolas Concha y Toro no Chile e Miolo no Brasil - Nyegray, João Alfredo Lopes (2013)
This dissertation addresses the possible correlations of the path of accumulation of technological capabilities in the internationalization process. This hypothetical influence was studied in Miolo Wine Group, in Brazil, and in Concha y Toro, in Chile. The study period is the same period of existence of the companies, from 1883 until 2013 of Concha y Toro, and from 1897 to 2013 for Miolo. The dissertation begins with a review of empirical studies that have explored on internationalization and technological capacity, and from that realizes the opportunity of theoretical and empirical concatenation of contextualizing this two areas of analysis to wineries. The relevance of this issue stems from the possible contribution to the strengthening of empirical studies that attempt to explain the phenomenon of internationalization of firms, and the differences between the companies that produce the same product and internationalize. To reach that goal the dissertation discusses the theories and models of internationalization and also the models of acquisition of technological capability. From the analysis of the theories, concepts and models, it adapts a model of acquisition of technological capability for the wine sector (adapted from Figueiredo, 2004), and adopts the model of internationalization of firms proposed by Kraus (2006). Both models have evolutionary view of the processes analyzed. The dissertation examines the different stages of internationalization of the wineries, which showed that each stage was necessary linked to a different technological capability. This dissertation found a deep and intimate relation between the internationalization process and developments in the accumulation of technological capabilities of the companies studied. It follows, then, that the wine industry companies aiming to conquer international markets with high quality demand and competitiveness, should engage in efforts to modernizing the use of technological capabilities as a mean to increase the quality of their wines.